Sistem Pembuangan Sampah Otomatis Berbasis IOT Menggunakan Mikrokontroler pada SMAN 14 Kab.Tangerang - Hani Dewi Ariessanti; Martono Martono; Joko Widiarto (CCIT Journal, 2019)
The use of automation in the control system as a means of efficiency of work has been commonly used and is a mechanism that runs automatically using a continuous media controller as instructed. At SMAN 14 Kab. Tangerang in order to improve the adiwiyata program must have a clean and well-run environment, but in the case of a garbage disposal system there are still shortcomings, namely the absence of information to school cleaners when the trash can is full so that the waste piles up, still using conventional methods of waste removal to the shelter. As well as a lack of information to the garbage truck officers who come so that the garbage piles up. With this research, an automatic waste disposal system was created which was intended as a tool to help work and provide hygiene information. The tool to be made consists of ultrasonic sensors and Wemos D1. Where the Ultrasonic sensor will provide volume information on the trash to Wemos D1 that is connected to Adafruit, if it is full Wemos D1 the shelter will retrieve data using the MQTT method. Next will take action to deliver the shelter to a full trash can through a linear actuator for disposal. By making this research can produce a tool with a control system automatically that helps human work as well as notifications regarding the capacity of the shelter and trash